Porta-enxertos para pereira (Pyrus sp.): implicações sobre a dormência, biologia floral e conteúdo de carboidratos. - Veríssimo, Valtair (2008)
Floral bud abortion has been the main limiting factor to the expansion of the pear crop in Brazil. That floral bud abortion has been considered as a complex problem that may be affected by physiological, sanitary, genetic and climatic factors. The rootstock that is the main subject of this study could also be an influencing factor in pear floral abortion, since until the year 2000, only the vigorous rootstocks Pyrus calleryana and Pyrus betulaefolia were used in Brazil. After that year, the pear growers of Santa Catarina and Rio Grande do Sul states started using dwarfing quince rootstocks such as Adams and EMC and the results has been satisfactory. In general these quince rootstocks are more sensitive to water stress during drought periods, since they develop a relatively small root system. However, the influence of these rootstocks on the physiology of dormancy, carbohydrate metabolism and floral biology are not known. With the objective of studying such unknown aspects, five experiments were carried out from 2005 to 2007 growth seasons. Part of these experiments was conduced under field conditions in a commercial orchard in Vacaria, RS, whereas other experiment activities were developed at Embrapa Clima Temperado research center in Pelotas, RS. All were composed of: a general literature review on the pear bud abortion subject, and plus five scientific articles, each one corresponding to one of the five above referred experiments. The first article contain the biological method to determine the dormancy level, on the pear cultivars Abbe Fetel and Packham s Triumph grafted on the quince rootstock EMC or Adams. The second article brings the results on carbohydrate levels in tissues of pear trees. The third article brings the results on floral biology of the above referred two cultivars on the two above referred quince rootstocks. The fourth article reports the results on the chilling requirement of potted trees of the pear rootstocks quinces EMC, EMA and Adams and of the pear rootstocks Pyrus calleryana and Pyrus betulaefolia, all them grown under controlled conditions. The fifth article reports the effects of chilling on potted trees of the pear cultivars Kieffer and Packham s Triumph grafted on the rootstocks quinces Adams, EMC or EMA, or on Pyrus betulaefolia, under controlled conditions. It were concluded that: the sugar transport and the floral biology were affected by rootstocks but not the dormancy development; the plants of the pear rootstocks quinces EMA, EMC and Adams have higher chilling requirements than the Pyrus calleryana and Pyrus betulaefolia rootstocks; the rootstock used changes the vegetative budbreak percentage of canopy cultivar; and that the higher chilling hours accumulated increased budbreak percentage and reduced floral bud abortion only until the chilling requirement is attained but floral bud abortion is increased after that condition.